2009
DOI: 10.2105/ajph.2007.131243
|View full text |Cite
|
Sign up to set email alerts
|

Racial/Ethnic Disparities in the Identification of Children With Autism Spectrum Disorders

Abstract: Objectives We sought to examine racial and ethnic disparities in the recognition of autism spectrum disorders (ASDs). Methods Within a multisite network, 2568 children aged 8 years were identified as meeting surveillance criteria for ASD through abstraction of evaluation records from multiple sources. Through logistic regression with random effects for site, we estimated the association between race/ethnicity and documented ASD, adjusting for gender, IQ, birthweight, and maternal education. Results Fifty-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
439
7
5

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 698 publications
(474 citation statements)
references
References 42 publications
23
439
7
5
Order By: Relevance
“…This current finding supports several previously published data that examine ASD among children stratified by race and ethnicity [18,19]. The observed higher prevalence of ASD among white children relative to blacks may be explained in part by appropriate diagnoses of ASD in whites, in contrast to blacks who may rather be diagnosed with attention deficit disorder (ADD) [20,19]. Additionally, black children may have less access to the healthcare system and may therefore be under-diagnosed with ASD [20].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This current finding supports several previously published data that examine ASD among children stratified by race and ethnicity [18,19]. The observed higher prevalence of ASD among white children relative to blacks may be explained in part by appropriate diagnoses of ASD in whites, in contrast to blacks who may rather be diagnosed with attention deficit disorder (ADD) [20,19]. Additionally, black children may have less access to the healthcare system and may therefore be under-diagnosed with ASD [20].…”
Section: Discussionsupporting
confidence: 89%
“…The observed higher prevalence of ASD among white children relative to blacks may be explained in part by appropriate diagnoses of ASD in whites, in contrast to blacks who may rather be diagnosed with attention deficit disorder (ADD) [20,19]. Additionally, black children may have less access to the healthcare system and may therefore be under-diagnosed with ASD [20]. We also surmised that the increasing prevalence of congenital anomalies among white children may contribute to the higher prevalence of ASD in whites, given the possibility of uterine environmental insult [3,11].…”
Section: Discussionmentioning
confidence: 99%
“…Potential parents seeking guidance for their reproductive decisions understandably may have difficulty comparing risks associated with age for different conditions, some of which carry considerable ambiguity in their diagnosis (Mandell et al 2009). The use of all-condition cognitive disability in this study, based on a large, population-based sample, contributes to our understanding of the overall risks.…”
Section: Discussionmentioning
confidence: 99%
“…The concerns of the WHO are well justified as studies have shown that cultural factors can potentially lead to health disparities in recognition, diagnostic assessment, and treatment for children with ASD especially regarding ethnic minority communities (Interagency Autism Coordinating Committee (IACC) 2014; Mandell et al 2002Mandell et al , 2009; National Autism Center 2015; Pierce et al 2014). Mandell and Novak (2005) argue that investigation of cultural factors in ASD research should focus on studying families' cultural views and beliefs about causes of their child's disability, existing barriers to ASD diagnosis as well as parents' treatment preferences.…”
Section: Introductionmentioning
confidence: 99%